SIVB: Pasang Surut Sepak Bola Bumiputera di Surabaya 1926 – 1942 - Widyatama, Fery; Febrianisah, Ragiel Rangga; Hanim, Fitria (KRONIK : Journal of History Education and Historiography, 2023)
Football in Indonesia started with the arrival of Europeans (Dutch) who initially worked in Dutch East Indies government agencies as employees of plantations, trade offices, shipping and mining. Apart from work, at that time, football was very popular with them because it had several benefits, including as a means of recreation and to maintain fitness by increasing muscle and bone strength. This sport is also in great demand by most of the indigenous people. This is evidenced by the many clubs or associations (bond) that have begun to emerge and develop in various regions, especially big cities in Java. One of the clubs or associations (bond) formed by indigenous people is SIVB (Soerabajasche Indonesische Voetbal Bond). During its development, SIVB Soerabaja showed its nationalism by participating in establishing the PSSI national football organization along with 6 other bonds in 1930.